Strategi Pemasaran Produk Program BPJS/JKN di Rumah Sakit Swasta - Ni Luh Putu Eka Karmila Dewi (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACT            The paradigm shift of service comparative advantage into competitive advantage currently affects the business competition of hospital services in Bali especially in BPJS/JKN and globalization. The emergence of Law no. 24 of 2011 on the Social Security Administering Agency, a challenge for the hospital industry, especially private hospitals, the policy has a big impact, especially the government targets in 2019 all the people of Indonesia are protected by BPJS/JKN. Can be imagined with global competition, maintaining the continuity of the hospital business and the obligation to synergize with government policy is a challenge in itself. Therefore, the hospital is required to determine market segmentation and create the right marketing strategy for BPJS/JKN program products by digging inputs and suggestions from internal and external customers, because they are the ones who will directly run and feel the service